The Integration of Vocabulary and Effective Sentence Mastery towards Students’ Argumentative Writing Skills - Tien Rafida (IAIN Salatiga, 2017)
The aims of this result to reveal the integrated of vocabulary and effective sentence mastery against the argumentation writing skill students’ PBI-SU FITK UIN the hypothesis proposed in this results are : (1) vocabulary mastery contribute to the argument to the arguments writing skill of students; (2) effective sentence mastery contribute to the argument writing skill of student; (3) vocabulary mastery and effective sentence mastery together contribute to the argument writing skill of students. This result uses a quantitative approach. The population in this study is PBI UIN-SU as many as 6 classes. As for the samples in this result are students of class II. By using cluster random sampling, obtained a sample of 140 students. The instrument used is a test. These results indicate that: (1) vocabulary mastery contributed positively and significantly to the argument essay writing skills of students. The amount of contribution is 18.4%; (2) Effective sentence mastery contribute positively and significantly to the argument essay writing skills of students. The amount of contribution is 11.7%; (3) mastery of vocabulary and mastery of effective sentences together contributed positively and significantly to the argument essay writing skills of students. The major contribution is 26.5%; (4) mastering vocabulary to effectively contribute by 16.39% against the argument essay writing skills of students; (5) Mastery effective sentence effectively contribute 13.11% against the argument essay writing skills of students. Based on the results of this study, it was concluded that the vocabulary and mastery of effective sentences are the two factors that influence the argument essay writing skills of students in addition to other factors. Therefore, the researchers suggest to all parties concerned to pay more attention to these two factors so that students' skills in essay writing can be further improved.